Engaging African Americans in Developing an Intervention to Reduce Breast Cancer Recurrence: A Brief Report - Selina Smith; Mary Whitehead; Joyce Sheats; Brittney Fontenot; Ernest Alema-Mensah; Benjamin Ansa (Georgia Southern University, 2016)
Background: To develop a culturally appropriate lifestyle intervention, involvement of its intended users is needed. Methods: Members of an African American (AA) breast cancer support group participated in two 4-hour guided discussions, which were audiotaped, transcribed, and analyzed to guide the content. Results: The support group collaborated with researchers to develop 24 experiential nutrition education sessions using a social cognitive framework and incorporating self-regulation skills (goal-setting, self-monitoring, problem-solving, stimulus control) and social support to enhance self-efficacy for changes in dietary intake. Conclusions: Community engagement fostered autonomy, built collaboration, and enhanced the capacity of AA breast cancer survivors to participate in developing a lifestyle intervention.